A financial planning model for retirement, taking into account the impact of pre-retirement funding income, age and taxation - Barnes, Andrew (Rhodes University, Faculty of Commerce, Department of Accounting, 2006)
Individuals are often not aware of the required level of contributions needed to fund a retirement savings plan. This problem is compounded by the fact that the assistance provided to these individuals by way of commercially-available retirement planning models does not take into account the effect of income tax on the level of required retirement savings contributions and recent changes in the tax legislation to the income tax payable by individuals has had a significant effect on these required levels. As a preamble to the research process, an exploratory questionnaire was administrated to a sample of individuals, which was designed to measure the level of awareness of these individuals of the contributions to a retirement savings plan needed to fund their postretirement financial needs, and of the impact of age, the level of income and income tax on their contributions. Responses to the questionnaire indicated a low level of awareness of retirement planning amongst these individuals. A retirement planning model was then designed to test the effect of earnings, age and changes in tax legislation on the level of an individual's required monthly contributions to a retirement savings plan. Independent variables of age and income were processed using the model. These same variables were then processed using the Old Mutual and Liberty Life retirement planning models and a comparison was made between the model developed in the research and these commercially developed models, to assess their usefulness and limitations. Based on the above comparison, it appeared that the Old Mutual and Liberty Life retirement models both included the effects of the individual marginal tax rates in their calculations. However, they appeared to be using marginal tax rates which were higher than those reflected in the 2006 individual income tax tables. In addition these models did not include the effect of income tax exemptions and deductions and they therefore provided more conservative estimates than the retirement planning model designed in the research. Recent tax adjustments have had the effect of greatly increasing the after-tax income of individuals and therefore it is important to include the effects of changes in tax legislation in determining the monthly contributions to a retirement savings plan.
Keywords: Retirement -- South Africa; Retirement income -- Planning -- South Africa; Pensions -- Planning -- South Africa; Finance, Personal; Investments; Income tax -- Law and legislation -- South Africa